2011
DOI: 10.1590/s1808-86942011000600017
|View full text |Cite
|
Sign up to set email alerts
|

Correlação entre equilíbrio corporal e capacidade funcional de idosos com disfunções vestibulares crônicas

Abstract: Vest ibular disorders are common among the elderly, mainly resulting in dizziness and imbalance -symptoms which can impact daily routine activities. Aim:To study the correlation between body balance and functional capacity and a comparison of risk of falls, actual falls and the functional capacity of the elderly with chronic vestibular dysfunctions. Materials and Methods:A cross-sectional, clinical and experimental study with 50 senior citizens -60 to 86 years, with chronic peripheral vestibular dysfunction. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 23 publications
0
8
0
3
Order By: Relevance
“…At second step of the study, the 223 patient's records were reviewed by the proposal of the Brazilian DGI-brief. Statistical date suggested11 points as cut the functional capacity and balance and negative correlation with risk for falls [4]. A study [5] noticed that there was influence of the cognitive function on the final scores of the DGI, and it referred no relation between risk for falls and quality of life in socially active elderly [6].…”
Section: Resultsmentioning
confidence: 99%
“…At second step of the study, the 223 patient's records were reviewed by the proposal of the Brazilian DGI-brief. Statistical date suggested11 points as cut the functional capacity and balance and negative correlation with risk for falls [4]. A study [5] noticed that there was influence of the cognitive function on the final scores of the DGI, and it referred no relation between risk for falls and quality of life in socially active elderly [6].…”
Section: Resultsmentioning
confidence: 99%
“…Dizziness is a common and troubling symptom in the elderly population (1, 2). Approximately 20% of the elderly living in a community report having dizziness severe enough to interfere with their routine activities (3).…”
Section: Introductionmentioning
confidence: 99%
“…The choice for this instrument may be more appropriate in specific populations, such as patients with vestibulopathy (13,20). Sousa et al (21) observed that nearly 60% of the individuals assessed with chronic vestibular dysfunctions presented risk of falls.…”
Section: Resultsmentioning
confidence: 99%